DENDROGRAMIC ANALITICAL STUDY OF REPORTED MASTREVIRUSES INFECTING MALVACEOUS AND FABACEOUS PLANTS USING BIOINFORMATICS TOOLS - ATIF, M; AHMAD, F; MANZOOR, MT; GILANI, K; ALI, Q; SARWAR, M; ANJUM, S; ALAM, MW; HUSSAIN, A (Biological and Clinical Sciences Research Journal, 2022)
The Chickpea Chlorotic Dwarf Virus (CpCDV) has been found devastating not only for chickpea crop but also for lentils, cotton and papaya. It has been found that up to 95% yield of crop plants have been reduced in dry regions of world including America and Europe. The vector species have also been found to play an important role for spreading of this virus form crop to crop and region to region. In our current study an evolutionary study of about 53 genomes was performed. According to our finding, the CpCDV is an important pathogen not only for the Fabaceae family but also has been reported found in Malvaceae family.